Prospek pengembangan industri perkulitan pada pelita VI - D Karyadi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1995)
The leather industry is one of the strong competitive industry, as it comes from renewable natural resources. Therefore, the leather industry has good prospect to develop at the Pelita VI to be the industrial products export competitive. To develop leather industry and leather products should be given closed attention and well managed, especially concerning raw material supply, quality and leather waste treatment. INTISARI Industri perkulitan merupakan salah satu industri berdaya saing kuat, karena berasal dari sumber daya alam yang dapat diperbaharui.Oleh karena itu industri perkulitan mempunyai prospek untuk dikembangkan pada Pelita VI untuk dijadikan komoditi andalan ekspor hasil-hasil industri.Untuk mengembangkan industri kulit dan produk kulit perlu diperhatikan dan dikelola dengan baik, hal-hal yang berkaitan dengan penyediaan bahan baku kulit, mutu dan pengendalian limbah kulit.